Cathodal tDCS Over Motor Cortex Does Not Improve Tourette Syndrome: Lessons Learned From a Case Series - Behler, Nora; Leitner, Bianka; Mezger, Eva; Weidinger, Elif; Musil, Richard; Blum, Bernhard; Kirsch, Beatrice; Wulf, Linda; Löhrs, Lisa; Winter, Christine; Padberg, Frank; Palm, Ulrich (Frontiers in Behavioral Neuroscience, 2018)
Introduction: Current pathophysiological hypotheses of Gilles de la Tourette Syndrome (GTS) refer to temporally abnormal neuronal activation in cortico-striato-thalamo-cortical networks. Modifying cortical activity by non-invasive brain-stimulation appears to be a new treatment option in GTS. Background: Previous studies suggested therapeutic effects of cathodal transcranial direct current stimulation (tDCS) to pre-supplementary motor areas (SMA), however, treatment modalities concerning electrode placement, current intensity and stimulation-rate have not been systematically explored. Aim of this study was to assess efficacy of an alternative stimulation regime on GTS symptoms in a pilot study. To test a treatment protocol with tDCS twice a day, we administered ten sessions over five days of bilateral cathodal tDCS (30 min, 2mA) over the pre-SMA in three patients with severe GTS. Tic severity as well as obsessive-compulsive (OC) symptoms and affective scales were rated before and after tDCS treatment. Discussion: Only one out of three patients showed a 34.5 % reduction in tic severity. The two other patients showed an increase in tic severity. All patients showed a mild increase in positive affect and a reduction in negative affect, OC symptom changes were heterogeneous. Our results do not support earlier findings of extensive therapeutic effects of cathodal tDCS on tics in patients with GTS and show that prediction of stimulation effects on a targeted brain area remains inaccurate. Concluding Remarks: Future research will have to focus on the determination of most effective stimulation modes regarding site, polarity, and frequency of tDCS in GTS patients.